Post dural puncture headache treated with steroids progressing to cerebral venous sinus thrombosis in a postpartum female: A case report - Ashok Jadon; Neelam Sinha; Priyanka Jain (Wolters Kluwer Medknow Publications, 2016)
Presentation of Cerebral venous sinus thrombosis (CVST) is clinically confusing. We present a case of 31 years an old postpartum woman who was treated with intravenous hydrocortisone for post dural puncture headache (PDPH) and developed CVST. We aim to present the diagnostic difficulties of such cases and the potential role of dural puncture and corticosteroids in the occurrence of CVST.